BO„LAJAK BOSHLANG„ICH SINF O„QITUVCHILARINI “TABIIY FANLAR VA ULARNI O„QITISH METODIKASI” FANI MAVZULARI ASOSIDA MA‟NAVIY FAOLIYATGA METODIK TAYYORLASH - Nabiyeva Dilfuza Temirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article prepares future elementary school teachers for lectures, seminars, practical, etc. Methodical preparation for the work of moral education of elementary school students in classes and extracurricular activities in elementary education "Science" (grades 1-2-3-4) about the possibilities.